Mesialización del sector posterior por la ausencia del primer molar mediante el uso de microimplantes - Pérez-Landeros, Matilde Valeria (2024)
A clinical case of a 16-year-old female patient is presented, who reported having lost her upper left first molar due to caries two years ago is presented. She is a patient with class II skeletal, mesofacial malocclusion, straight profile, class I right molar, absence of tooth 26, class I right canine and tendency to class II left canine, with mild upper and lower crowding and lower dental midline deviated to the left. It was treated through the use of a microimplant, with the objective of mesializing teeth 27 and 28 as well as improving the settlement of the left canine class. The mesialization of the upper left posterior teeth was successfully completed, establishing adequate occlusion, eliminating crowding, achieving good anterior guidance with coincident dental midlines, providing a functional and harmonious smile. The purpose of this case is to demonstrate that with the appropriate tools and mechanics in addition to good planning, control of the anchorage in the posterior closing movement can be achieved in the absence of an absent molar, and thus achieve adequate occlusion.